2014
DOI: 10.1097/dcr.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Lymph Node Recurrence in the Untreated Groin of Patients with Anal Carcinoma

Abstract: Elective irradiation of the groin should be considered for local control in patients (N0-N1) with T2 tumors ≥4 cm in size and/or located in the perianal skin, and in all patients with T3 and T4 tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…These studies showed that inguinal node radiation achieved excellent nodal control, and the inguinal node should be involved in the radiation field. Blinde et al found that the 5-year inguinal recurrence rate was high in patients who did not receive elective irradiation therapy to the groin and suggested that elective irradiation of the groin should be considered for local control 31. The results of the Trans-Tasman Radiation Oncology Group study (TROG) 99.02 also showed that T1-2 anal carcinomas require elective inguinal radiation treatment 32.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that inguinal node radiation achieved excellent nodal control, and the inguinal node should be involved in the radiation field. Blinde et al found that the 5-year inguinal recurrence rate was high in patients who did not receive elective irradiation therapy to the groin and suggested that elective irradiation of the groin should be considered for local control 31. The results of the Trans-Tasman Radiation Oncology Group study (TROG) 99.02 also showed that T1-2 anal carcinomas require elective inguinal radiation treatment 32.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the importance of elective groin irradiation especially for T3-T4 tumors. Among patients with uninvolved inguinal nodes at diagnosis who did not receive elective radiation to the groin the inguinal recurrence rates for T1-2N0 tumors range from 5% to 13%, while for T3-4N0 tumors it is 6-30% [9][10][11][12][13]. Matthews et al prematurely closed a study (T1-2N0, no radiation to the groins) because of an unacceptable high inguinal relapse of 22.5% after three years [14].…”
Section: Introductionmentioning
confidence: 99%
“…The indication of prophylactic inguinal irradiation is, however, controversial. According to the two largest retrospective studies 4,5 it is clear that treating or not the inguinal LNs based only on the T stage has a large risk of over/under-treatment. A better detection of early inguinal LNs involvement could properly select patients who really deserve inguinal irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 270 patients who did not receive prophylactic inguinal irradiation, after a median follow-up of 72 months, the incidence of inguinal metastases was 8% 3 . Two retrospective studies reported the inguinal recurrence rate in patients staged with conventional examinations who did not receive prophylactic inguinal irradiation: Blinde et al 4 showed inguinal recurrence rate of 0% in T1, 10% in T2 and 20% in T3–T4 patients with a median follow-up of 65 months, and Ortholan et al 5 reported an inguinal recurrence rate of 12% for T1–T2, and 30% for T3–T4 patients with a median follow-up of 61 months. As a consequence, the prescription of prophylactic inguinal irradiation based only on the T stage would cause an unnecessary irradiation of about 70–80% of T3–T4 patients, submitting them to a risk of severe acute toxicity, especially when using conformal RT techniques 6 .…”
Section: Introductionmentioning
confidence: 99%